A Novel Ultra-Broadband Low-Loss Bond-Wire Interconnect Design Concept Applied to a 2 GHz to 135 GHz Substrate-to-Substrate Interface - Pfahler, Tim; Scheder, André; Bridier, Anna; Schür, Jan; Vossiek, Martin (2023 IEEE/MTT-S International Microwave Symposium - IMS 2023, 2023)
This work presents a design concept for ultra-broadband bond-wire interconnects between two alumina substrates from 2 GHz up to 135 GHz. Due to the rethinking of the substrate assembly and optimization of the CPW bond-wire transmission line interface, the currently existing limitations in terms of a narrowband matching bandwidth and high insertion loss of state-of-the-art interconnects can be eliminated. The resulting key advantage of the proposed design is the ultra-broadband characteristic that exhibits lowest impedance discontinuity and thus realizing an excellent matching bandwidth of more than 130 GHz. The measured return loss is higher than 25 dB with an insertion loss of less than 1.6 dB over the entire frequency band. The paper highlights both, the electric considerations as signal routing and the assembly part for achieving a robust, reproducible and fully mmW-transparent interconnect even beyond 100 GHz. Due to the broadband performance and the high agreement of simulation and measurement results the proposed interconnect and the underlying design and assembly considerations set a new benchmark for interconnect design. Moreover, this approach can be used for signal transitions in applications such as broadband communication systems, high-resolution radar sensing and measurement and test applications.<br